Implementation outcomes of cognitive behavioural therapy delivered by non-specialists for common mental disorders and substance-use disorders in low- and middle-income countries: a systematic review - Verhey, Ibone J. (Int J Ment Health Syst, 2020)
Due to severe shortages of specialist mental health personnel in low- and middle-income countries (LMICs), psychological therapies are increasingly being delivered by non-specialist health workers (NSHWs). Previous reviews have investigated the effectiveness of NSHW-delivered psychological therapies, including cognitive behavioural therapy (CBT), in LMIC settings. This systematic review aims to synthesise findings on the implementation outcomes of NSHW-delivered CBT interventions addressing common mental disorders and substance-use disorders in LMICs. Four databases were searched, yielding 3211 records, 18 of which met all inclusion criteria. We extracted and synthesised qualitative and quantitative data across eight implementation outcomes: acceptability, adoption, appropriateness, feasibility, fidelity, implementation cost, penetration and sustainability. Findings suggest that delivery of CBT-based interventions by NSHWs can be acceptable, appropriate and feasible in LMIC settings. However, more research is needed to better evaluate these and other under-reported implementation outcomes.